Knot positioning during McDonald cervical cerclage, does it make a difference? A cohort study. (17th November 2019) - Atia, Hytham; Ellaithy, Mohamed; Altraigey, Ahmed; Ibrahim, Heba
Abstract: Objective: To study the effect of McDonald cerclage knot position on the different maternal and neonatal outcomes. Methods: This historical cohort study included women with singleton pregnancy who had a prophylactic McDonald cervical cerclage between 1 May 2010 and 31 September 2017. Maternal and neonatal outcome parameters were compared between the anterior and posterior knot cerclage procedures. The primary outcome measure was the rate of term birth. Results: 550 Women had a prophylactic McDonald cervical cerclage, 306 with anterior knot (Group A) and 244 with posterior knot (Group B). There were no statistically significant differences regarding gestational age (GA) at delivery (36.3 ± 4.2 versus 35.8 ± 5.3 for groups A and B respectively), term birth rate, post-cerclage cervical length, symptomatic vaginitis, urinary tract infection, difficult cerclage removal and cervical lacerations. Similarly, there were no statistically significant differences as regards the studied neonatal outcomes including take home babies, neonatal intensive care admission, respiratory distress syndrome and neonatal sepsis. Survival analysis on GA at delivery demonstrated no statistically significant difference as regards the proportion of term deliveries in the anterior and posterior knot cerclage groups (log-rank test p -value = .478). Conclusions: Knot positioning during McDonald cervical cerclage, anteriorly or posteriorly, didn't significantly impact the studied maternal and neonatal outcomes.